Relationship between Customer Loyalty, Customer Satisfaction, Customer Trust, and Service Quality in E-Commerce Setting: Case Study of Lazada in Indonesia - Yulita Fairina Susanti; Albert Hasudungan; Arif Wiratama Prasetyo (International Journal of Business Studies, 2018)
The main objective of this study is to examine the relationship of each dimension of Service Quality to Customer Satisfaction and Customer Trust, Customer Satisfaction to Customer Trust and Customer Loyalty, and Customer Trust to Customer Loyalty. The sampling is selected on the basis of random sampling from Jakarta Millennial generation, below 31 years old, that use online transaction. The questionnaire was distributed in 2017 to that Jakarta Millennial respondents on the basis of random sampling selection. This study uses Covariance-Based Structural Equation Modelling, and the variable is adopted by the previous study to see that relationship. The research finds that Website Design, Responsiveness, and Assurance has signiicant effect to Customer Satisfaction, Customization and Assurance has significant effect to Customer Trust, Customer Satisfaction has significant effect to Customer Trust and Customer Loyalty, and Customer Trust has significant effect to Customer Loyalty. This study recommends equal proportion of business efforts between the service delivery and customize technology to retain their customer loyalty, since the results underscore the importance of both technical and service delivery aspects.